When energy justice is contested: A systematic review of a decade of research on Sweden's conflicted energy landscape. (December 2022) - Ramasar, Vasna; Busch, Henner; Brandstedt, Eric; Rudus, Krisjanis
Abstract: The way in which we produce and consume energy has profound implications for our societies. How we configure our energy systems determines not only our chances of successfully dealing with climate change but also, how benefits and burdens of these systems are distributed. In this paper, we set out to map the literature on conflicts related to the energy system in Sweden using a framework of energy justice. The purpose of this exercise is twofold: first, to identify and understand energy conflicts in Sweden through the research that is published; and second, to identify gaps in the literature on energy justice in Sweden. This systematic review builds upon 40 scholarly articles focusing on energy conflicts in Sweden. All articles were written in the time period from January 2010 to January 2021. All articles were published in English in peer-reviewed scientific journals. The papers were analysed using a framework for energy justice that focused on the elements of distributional and procedural justice and recognition justice. The findings of the review suggest that there has been little explicit focus on energy justice in the literature on Sweden's energy system. Issues of distributional justice are most raised and procedural and recognition justice are often conflated in research. While conflicts over hydropower and nuclear have dominated in the past, wind energy in Sami territory is most problematised in the reviewed literature. The understanding of justice in the Swedish energy system is currently missing two elements: a rigorous handling of ecologically unequal exchange and restorative justice.